The Effect of Husband's Knowledge and Support on Complete Visit for Pregnant Mothers at Sitiung Health Center 1 - Sukmawati Sukmawati; Sri Andar Puji Astuti; Frens Tika Veriyani; Eni Yuliawati (Science Midwifery, 2022)
The government has made various efforts to reduce the MMR, one of which is through routine examinations of pregnant women. Visits of pregnant women have increased every year. However, the decline occurred in 2020, from 88.54% in 2019 to 84.6% in 2020. The province of West Sumatra itself is still low in terms of K4 visits, namely the Province with the 23rd order of 34 provinces in Indonesia by reaching K4 72.8% in 2020. This research method uses an analytical survey using a Cross Sectional approach. This research was conducted in the working area of the Sitiung 1 Public Health Center, Dharmasraya Regency in April-May 2021. The population in this study was 102 pregnant women and the sample was taken using a purposive sampling technique using the slovin formula. So that the sample in this study was 50 samples. The results are based on the results of the Pearson correlation variable that the independent husband's knowledge and support has a strong and positive relationship with the dependent variable of complete visits. The value of knowledge on complete visits (r = 0.612) and husband's support variable on complete visits (r = 0.752). The multivariate test got the equality of knowledge and husband's support increased by 1 point, then the return visit of pregnant women would increase by (5.999 + (0.111 x 50) + (0.102 x 50) = 16.64.